2022
DOI: 10.1111/cpr.13294
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the interaction between N6‐methyladenosine methylation and noncoding RNAs in musculoskeletal disorders

Abstract: Background: Musculoskeletal disorder (MSD) are a class of inflammatory and degener-ative diseases, but the precise molecular mechanisms are still poorly understood. Noncoding RNA (ncRNA) N6-methyladenosine (m6A) modification plays an essential role in the pathophysiological process of MSD. This review summarized the interaction between m6A RNA methylation and ncRNAs in the molecular regulatory mechanism of MSD. It provides a new perspective for the pathophysiological mechanism and ncRNA m6A targeted therapy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 202 publications
0
23
0
Order By: Relevance
“…[44][45][46] Significantly, a major regulatory function of nuclear lncRNAs is the modulation of the activity of several critical genes by coordinating with DNA epigenetic regulators, thus epigenetically influencing gene expression. 47 The majority of GRIK1-AS1 was found in the nucleus, and GRIK1-AS1 may directly interact with the DNA epigenetic controller DNMT1. Notably, our ROC curve analysis revealed that the better predictive performance that GRIK1-AS1 can be of prognostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46] Significantly, a major regulatory function of nuclear lncRNAs is the modulation of the activity of several critical genes by coordinating with DNA epigenetic regulators, thus epigenetically influencing gene expression. 47 The majority of GRIK1-AS1 was found in the nucleus, and GRIK1-AS1 may directly interact with the DNA epigenetic controller DNMT1. Notably, our ROC curve analysis revealed that the better predictive performance that GRIK1-AS1 can be of prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The essential roles of nucleus‐located lncRNAs are chromatin reorganization and transcription regulation 44–46 . Significantly, a major regulatory function of nuclear lncRNAs is the modulation of the activity of several critical genes by coordinating with DNA epigenetic regulators, thus epigenetically influencing gene expression 47 . The majority of GRIK1‐AS1 was found in the nucleus, and GRIK1‐AS1 may directly interact with the DNA epigenetic controller DNMT1.…”
Section: Discussionmentioning
confidence: 99%
“…The above finding proved that the potential regulatory mechanism of m6A regulators modulated the process of OP. MiRNAs and lncRNAs are two targets that have recently come into the spotlight due to their regulatory ability to affect gene expression at the transcriptional or post-transcriptional levels and provide epigenetic modification ( 54 , 60 , 61 ). Here, we found that an m6A regulator (METTL3) and three m6A targets (SMAD4, HIPK3, and EGFR) might have a function in OP in an lncRNA–miRNA-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although the five-year survival was elevated over the last 3 decades for the OS population, their prognosis is still poor, making it necessary to discover new diagnostic and therapeutic targets for the management of OS [ 19 , 20 , 21 ]. The advantages of circRNA, such as its structural stability and tissue specificity, have attracted the attention of researchers in recent years [ 22 , 23 ]. Recent evidence suggests the close association of circRNA dysregulation with carcinoma progression and metastasis, including OS, indicating its potential as an OS therapeutic target [ 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%